Church-Based Environmental Communication for Ecological Advocacy: Insights from "Laudato Si’" - Chacko, Amala T. (2026)
The escalating environmental crisis demands urgent action from all sectors of society, including religious institutions. The Catholic Church, with its global influence and moral authority, has taken a significant stance on ecological issues through Laudato Si’, Pope Francis’s 2015 encyclical on environmental stewardship. Laudato Si’ calls for a comprehensive ecology that acknowledges and addresses the interdependence of ecological, social, and economic systems and challenges people, communities, and governments to undergo an ecological conversion. This article discusses the importance of Church-based environmental communication in facilitating ecological advocacy and examines the strengths and challenges in the religious setting. The Church can contribute to a sustainable future by helping overcome communication barriers, building faith-based ecological education, and popularizing digital platforms. The results address the necessity of long-term dedication and creativity in environmental advocacy within religious environmentalism, making sure that Laudato Si’ is not another theological treatise, but an action plan.